Estratificación del riesgo de cardiotoxicidad inducida por quimioterapia: Respuesta - Morales Yera, Rodolfo A.; Sierra Pérez, Ludmila; Triana Díaz, Alexander (CorSalud, 2018)
Estratificación del riesgo de cardiotoxicidad inducida por quimioterapia: Respuesta